Einfluss der Sichtradgeometrie auf die Sichtluftströmung und Partikelbewegung eines Abweiseradsichters. Issue 4 (16th February 2018) - Spötter, Christian; Legenhausen, Kurt; Weber, Alfred P.
Abstract: In the industrial preparation of fine particles, the classification in a deflector wheel classifier is an important step for the production of many highly specified products. Previous experiments have shown that fluid vortices are formed between the paddles of the classifying wheel, which significantly influence the fluid flow, the particle movement, and, finally, the separation properties of the classifier. Therefore, it is the aim of the present work to uncover the relationship between paddle geometry, fluid flow, and separation characteristics.